Regulation by Polyamines of Ornithine Decarboxylase Activity and Cell Division in the Unicellular Green Alga Chlamydomonas reinhardtii - Theiss, Christine (American Society of Plant Physiologists, 2002)
Polyamines are required for cell growth and cell division in eukaryotic and prokaryotic organisms. In the unicellular green alga Chlamydomonas reinhardtii, biosynthesis of the commonly occurring polyamines (putrescine, spermidine, and spermine) is dependent on the activity of ornithine decarboxylase (ODC, EC 4.1.1.17) catalyzing the formation of putrescine, which is the precursor of the other two polyamines. In synchronized C. reinhardtii cultures, transition to the cell division phase was preceded by a 4-fold increase in ODC activity and a 10- and a 20-fold increase, respectively, in the putrescine and spermidine levels. Spermine, however, could not be detected in C. reinhardtii cells. Exogenous polyamines caused a decrease in ODC activity. Addition of spermine, but not of spermidine or putrescine, abolished the transition to the cell division phase when applied 7 to 8 h after beginning of the light (growth) phase. Most of the cells had already doubled their cell mass after this growth period. The spermine-induced cell cycle arrest could be overcome by subsequent addition of spermidine or putrescine. The conclusion that spermine affects cell division via a decreased spermidine level was corroborated by the findings that spermine caused a decrease in the putrescine and spermidine levels and that cell divisions also could be prevented by inhibitors of S-adenosyl-methionine decarboxylase and spermidine synthase, respectively, added 8 h after beginning of the growth period. Because protein synthesis was not decreased by addition of spermine under our experimental conditions, we conclude that spermidine affects the transition to the cell division phase directly rather than via protein biosynthesis.